1996
DOI: 10.1007/bf02845090
|View full text |Cite
|
Sign up to set email alerts
|

On separation axioms in hyperspaces

Abstract: It is the purpose of this paper to show how to use approach spaces to get a unified method of proving Baireness of various hyperspace topologies. This generalizes results spread in the literature including the general (proximal) hit-and-miss topologies, as well as various topologies generated by gap and excess functionals. It is also shown that the Vietoris hyperspace can be non-Baire even if the base space is a 2nd countable Hausdorff Baire space.2010 MSC: Primary 54B20; Secondary 54E52, 54A05

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…It was observed that imposing separation axioms on the base space is frequently not necessary to obtain results on hypertopologies (see [6], [19], [24], [10]), which is the case throughout this paper as well.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…It was observed that imposing separation axioms on the base space is frequently not necessary to obtain results on hypertopologies (see [6], [19], [24], [10]), which is the case throughout this paper as well.…”
Section: Introductionmentioning
confidence: 85%
“…15, no. 1 This property is satisfied in uniform and metric spaces, and a topological space X has property (P) iff X is weakly-R 0 [24], i.e. for all open U ⊆ X and x ∈ U there is a y ∈ {x} with {y} ⊂ U iff each nonempty difference of open sets contains a nonempty closed set.…”
Section: Hyperspace Topologiesmentioning
confidence: 99%
“…This is a continuation of [19]. We characterize first and second countability of the general hit-and-miss hyperspace topology for weakly-base spaces.…”
Section: László Zsilinszkymentioning
confidence: 95%
“…be a topological space and be the nonempty closed subsets of . Following [2], [3], [5], [16], [17], [19], [20], [21] we will continue to study hit-and-miss hyperspace topologies or -topologies on , where is a fixed subfamily of . Two of the most studied hit-and-miss topologies are the Vietoris topology ( [14], [13]) and the Fell topology ( [7], [13], [17]).…”
Section: Letmentioning
confidence: 99%
See 1 more Smart Citation